2019
DOI: 10.1080/15548627.2019.1582743
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 promotes antimycobacterial defenses by coordinating mitochondrial and autophagic functions

Abstract: SIRT3 (sirtuin 3), a mitochondrial protein deacetylase, maintains respiratory function, but its role in the regulation of innate immune defense is largely unknown. Herein, we show that SIRT3 coordinates mitochondrial function and macroautophagy/autophagy activation to promote anti-mycobacterial responses through PPARA (peroxisome proliferator activated receptor alpha). SIRT3 deficiency enhanced inflammatory responses and mitochondrial dysfunction, leading to defective host defense and pathological inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 66 publications
6
94
0
Order By: Relevance
“…Several colitogenic bacteria promote inflammatory conditions that favor their own growth. Hence, inefficient clearance of bacteria results in non‐resolving inflammation, followed by increased pro‐inflammatory responses 57,58 . These findings suggest Ninj1 deficiency may contribute to microbial imbalance by increasing basal colonic inflammation due to defective bacterial lysis in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Several colitogenic bacteria promote inflammatory conditions that favor their own growth. Hence, inefficient clearance of bacteria results in non‐resolving inflammation, followed by increased pro‐inflammatory responses 57,58 . These findings suggest Ninj1 deficiency may contribute to microbial imbalance by increasing basal colonic inflammation due to defective bacterial lysis in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Cxcl5 mRNA level was significantly increased in macrophages and epithelial cells in Sirt3-deficient lung during M. tuberculosis infection [47]. Neutrophil depletion by targeting Ly6G reportedly enhances host defense against M. tuberculosis infection in mice [46][47][48]. In addition, whether CXCL10 is increased in Mabc patients or Mabc infection models is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung of Ppara -/mice, Cxcl5 and Cxcl10 expression levels were significantly increased. The chemokine CXCL5 is involved in the regulation of neutrophil influx and pulmonary neutrophil inflammation during M. tuberculosis infection [46][47][48]. In addition, the Cxcl5 mRNA level was significantly increased in macrophages and epithelial cells in Sirt3-deficient lung during M. tuberculosis infection [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research showed that some sirtuin family members, including Sirt1 and Sirt3, can bind and deacetylate ATG5, allowing phagophore elongation and maturation into a double-membrane autophagosome [22,37,38]. To examine if the Sirt3/ATG5 interaction is promoted by ES in our macrophage model of VbPinduced pyroptosis, we first combined MitoTracker staining and immunofluorescence and found that both Sirt3 and ATG5 were predominately expressed in mitochondria ( Supplementary Figure 1).…”
Section: Es Promotes Deacetylation Of Atg5 By Upregulating Sirt3mentioning
confidence: 99%